Targeted therapy for breast cancer and molecular mechanisms of resistance to treatment. (December 2016) - Gu, Guowei; Dustin, Derek; Fuqua, Suzanne AW
Highlights: Remarkable progress has been made in targeted therapies in ER positive or HER2 positive MBC. Personalized therapy should be applied to guide targeted therapy in TNBC. Optimization of patient selection and predictive biomarkers development are urgently required to improve clinical trial design. Longitudinal monitoring of plasma DNA should be considered to guide treatment in MBC. Abstract : In recent years, clinical trials investigating new drugs and therapeutic combinations have led to promising advances in breast cancer therapy. Subtyping breast cancers into hormone receptor (HR) positive, epidermal growth factor receptor (HER2) positive, and triple negative breast cancer (TNBC) is currently the basis of diagnosing and treating this disease. In addition to endocrine and HER2-targeted therapies in their respective subtypes, evidence from recent preclinical studies have shown several targetable pathways that overcome resistance in the clinical setting. The mTOR inhibitor everolimus and the CDK4/6 inhibitor palbociclib have been approved in HR-positive metastatic breast cancer (MBC) due to improved disease-free survival (DFS). Adding pertuzumab to trastuzumab in combination with taxanes further improves DFS in HER2-positive breast cancer. Targeted therapy to the heterogeneous group of TNBC is needed in combination with chemotherapy. However, patient selection and predictive biomarker development remains a big challenge for targeted therapy development in TNBC.